Variations sur la victime et la justice pénale internationale - Julian Fernandez (Amnis)
For a long time, the victim of serious violations regarding humanitarian international law had been ignored by the new field of international criminal Justice. However, the benefit of an enlightened justice would be – no doubt – an important parameter in the process of “resilience” for the victims of the horror, who are unable to face a post traumatic everyday life. Recently, the core rights of the victims before international criminal justice (representation, protection, compensation) has been taking into account by the international criminal Court, demonstrating a promising but still fragile evolution.